2012
DOI: 10.1073/pnas.1200521109
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and plasticity in RNA-protein interactions enable recruitment of multiple proteins through a single site

Abstract: mRNA control hinges on the specificity and affinity of proteins for their RNA binding sites. Regulatory proteins must bind their own sites and reject even closely related noncognate sites. In the PUF [Pumilio and fem-3 binding factor (FBF)] family of RNA binding proteins, individual proteins discriminate differences in the length and sequence of binding sites, allowing each PUF to bind a distinct battery of mRNAs. Here, we show that despite these differences, the pattern of RNA interactions is conserved among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
56
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 49 publications
7
56
0
Order By: Relevance
“…With amino acid numbering relative to the PUF domain, two "edge-on" residues at motif positions 12 and 16 make hydrogen bonds and van der Waals contacts with the Watson-Crick edge of the RNA base, and the residue at position 13 forms planar stacking interactions with the aromatic ring of the base, together resulting in base-specific binding ( Fig. 2A) (61)(62)(63)(65)(66)(67). Using MUSCLE (68), we compared 109 PUF motif sequences of KREPB5, KREPB4, KREN1, KREN2, and KREN3 from a range of kinetoplastid species and 17 proteins with multiple repeats from human, Drosophila melanogaster, Saccharomyces cerevisiae, and Caenorhabditis elegans (supplemental Fig.…”
Section: Krepb5 Is Essential In Both Bf and Pf T Brucei-knock-mentioning
confidence: 99%
“…With amino acid numbering relative to the PUF domain, two "edge-on" residues at motif positions 12 and 16 make hydrogen bonds and van der Waals contacts with the Watson-Crick edge of the RNA base, and the residue at position 13 forms planar stacking interactions with the aromatic ring of the base, together resulting in base-specific binding ( Fig. 2A) (61)(62)(63)(65)(66)(67). Using MUSCLE (68), we compared 109 PUF motif sequences of KREPB5, KREPB4, KREN1, KREN2, and KREN3 from a range of kinetoplastid species and 17 proteins with multiple repeats from human, Drosophila melanogaster, Saccharomyces cerevisiae, and Caenorhabditis elegans (supplemental Fig.…”
Section: Krepb5 Is Essential In Both Bf and Pf T Brucei-knock-mentioning
confidence: 99%
“…Saccharomyces cerevisiae Puf3p, Puf4p, and Puf5p represent the cytoplasmic clades, which include the human PUM1/Pumilio (1). Puf3p binds the RNA sequence 5′UGUANAUA3′, while yeast Puf4p and Puf5p bind UGUR (R, purine)-containing sites, but exhibit variations in length and sequence (10).…”
mentioning
confidence: 99%
“…However, a similar pocket was found in FBF by re-examining FBF target sequences and allowing an upstream C to be present at either the -2 or -1 position [38]. In another case, yeast Puf4 was found to bind a second subset of nine-base sequences by excluding a different base from recognition [39]. This additional binding mode suggested mechanisms for co-regulation of mRNAs by multiple PUF proteins and evolution of RNA regulatory networks.…”
Section: Natural Puf Protein Rna Recognition Modesmentioning
confidence: 86%
“…Most classical PUF proteins recognize a 5′-UGUR element (R=purine) and a downstream UA element, and the characteristic recognition sequences of individual PUF proteins vary in the number of bases between the UGUR and UA elements [39]. Some of the first studies identifying target mRNAs of S. cerevisiae Puf4 [36] and C. elegans FBF [12, 42] proteins revealed that they recognize nine-base consensus sequences, one base longer than expected for their eight repeats.…”
Section: Natural Puf Protein Rna Recognition Modesmentioning
confidence: 99%